2017
DOI: 10.1111/acv.12370
|View full text |Cite
|
Sign up to set email alerts
|

Hand feeding can periodically fuel a major portion of bull shark energy requirements at a provisioning site in Fiji

Abstract: Wildlife tourism is often extolled for its contribution to conservation. However, understanding the effects of tourism activities on the health of target animals is required to fully assess conservation benefits. Shark tourism operators often use food rewards to attract sharks in close proximity to tourists, but nothing is known about the contribution of these food rewards to the energetic requirements of target species. In this study, hand feeding of bull sharks Carcharhinus leucas was directly observed on 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Negative effects resulting from tourist activities have been observed in other marine protected species, such as marine birds and cetaceans, where interruptions in foraging and breeding have been linked to a higher use of energy (Green & Giese, ). Nevertheless, intentional and supplementary feeding would not necessarily affect the energy balance or feeding ecology in elasmobranchs, as it has been observed in bull sharks ( Carcharhinus leucas ) during the ecotourism in Fiji (Abrantes, Brunnschweiler, & Barnett, ; Brunnschweiler, Payne, & Barnett, ). However, the energy expenditure due to a lack of food reward is beyond the scope of this study and should be assessed in future research regarding baits and white shark physiology during ecotourist activities.…”
Section: Discussionmentioning
confidence: 99%
“…Negative effects resulting from tourist activities have been observed in other marine protected species, such as marine birds and cetaceans, where interruptions in foraging and breeding have been linked to a higher use of energy (Green & Giese, ). Nevertheless, intentional and supplementary feeding would not necessarily affect the energy balance or feeding ecology in elasmobranchs, as it has been observed in bull sharks ( Carcharhinus leucas ) during the ecotourism in Fiji (Abrantes, Brunnschweiler, & Barnett, ; Brunnschweiler, Payne, & Barnett, ). However, the energy expenditure due to a lack of food reward is beyond the scope of this study and should be assessed in future research regarding baits and white shark physiology during ecotourist activities.…”
Section: Discussionmentioning
confidence: 99%
“…Our work represents an important first step in understanding how the ecology of coral reefs is impacted by tourism. Stable isotope studies have suggested that food provisioning at Beqa shark dive sites could meet daily nutritional diets for some bull sharks [17] Whether the tuna subsidy to smaller, opportunistically feeding species is energetically significant for other species remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…In some ways, commercial shark feeding mimics natural exploitation of hyperabundant resources [15] as pelagic fish (tuna heads) are fed to the sharks, thus providing a human-facilitated trophic linkage between pelagic and near-shore systems. In fact, while a recent isotopic study suggested that trophic supplementation to bull sharks ( Carcharhinus leucas ) from tuna heads represented only a minor component of their diet [16], a bioenergetics model suggested that at least some sharks could meet or exceed their daily dietary requirements solely from provisioned food [17]. Thus at least on local time scales, tourism-based provisioning can provide an important role in the population ecology of reef apex predators.…”
Section: Introductionmentioning
confidence: 99%
“…pinnipeds). Whether the infrequent consumption of these baits provide sufficient energy to compensate for the increased energy expenditure associated with sharks interacting with the operators would depend on the calorific value of these baits and the frequency of white sharks successfully feeding on the baits, both of which are currently unknown ( Brunnschweiler et al , 2017 ). Spending time interacting with cage-diving operators might also distract sharks from normal behaviours such as foraging on natural, energy-rich prey like pinnipeds.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should quantify the amount of time white sharks interact with cage-diving operators and estimate its effect on white sharks in relation to their daily energy budget. Estimation and comparison of the energy obtained from natural prey vs. bait would also facilitate a better understanding of the effect of the cage-diving industry on the energy budget of white sharks ( Brunnschweiler et al , 2017 ). Such information will enable managers to go beyond the use of presence/absence of cage-diving vessels and sharks and account for the potential effect of wildlife tourism on the energy balance, fitness and ultimately population viability of this internationally threatened species.…”
Section: Discussionmentioning
confidence: 99%